2018
DOI: 10.1093/infdis/jiy317
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlations of Transcriptional Profile in Patients Infected With Avian Influenza H7N9 Virus

Abstract: This study correlated serial blood transcriptomic profiles of patients with avian influenza A (H7N9) virus infection with clinical data of patients. Biologically significant transcriptomic profiles associated with blood oxygenation and viral load in the lower respiratory tract were defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Robust multi-factorial immune responses can be elicited against viral infection, such as avian H7N9 disease 17,18 . A recent report has found effective immune responses from a non-severe COVID-19 patient 19 .…”
mentioning
confidence: 99%
“…Robust multi-factorial immune responses can be elicited against viral infection, such as avian H7N9 disease 17,18 . A recent report has found effective immune responses from a non-severe COVID-19 patient 19 .…”
mentioning
confidence: 99%
“…Notably, gene expression changes persisted up to 1 month after infection. Similarly, studies of H7N9 infected patients showed transcriptional profile changes persisting up to 1 month with a transition from innate to adaptive immunity [86].…”
Section: Mechanisms Of Diseasementioning
confidence: 92%
“…However, direct links of events to viral infection are scarce in part due the event of interest may follow the infection by several weeks when the virus is no longer detectable by traditional testing. Several gene profiling studies have identified viral infection signatures that may persist up to 1-month post infection [79,86]. Thus, it might be possible to study patients with falls or cardiac events for evidence of recent viral infection using a host response viral signature.…”
Section: Associations With Respiratory Viral Infection With Non-respimentioning
confidence: 99%
“…In April 2019 a fatal 66 case of highly pathogenic avian influenza (HPAI) H7N9 was reported in Inner Mongolia, China, 67 which was associated with severe pneumonia and respiratory failure [2]. Acute respiratory distress 68 syndrome, as observed in the recent human case of HPAI H7N9 infection, may be caused by multiple 69 factors, including higher viral load [3], altered viral tropism and spread in the lower/upper respiratory 70 tract [4], virally-induced host shutoff [5] or hijacking host function [6][7][8][9]. Mass spectrometry-based 71 serum proteome profiling has made it possible to conduct extracellular fluid proteins analysis and to 72 4 investigate important mediators of intercellular communication and host-viral interactions associated 73 with disease progression, coagulation, communication, inflammation and the immune response.…”
Section: Introduction 64mentioning
confidence: 99%
“…Our study identified key host responses that may 96 be related to the progression of H7N9 disease. 97 Supplementary Table 2; and clinical and 108 immunological features of some patients have been reported [3,14]. Ten healthy serum controls were 109 collected from our lab colleagues.…”
Section: Introduction 64mentioning
confidence: 99%